In search of a healthy way of living: story of experience with a group of aged registered in the family’s health program in Pacatuba-CE - Patrícia Maria Tavares Cavalcante; Maria Célia de Freitas (Rev Rene)
The aim of the study was to report the experience of working with a group of elderly people registered in the program health of the family in Pacatuba-CE in the leisure time as well as other activities. A profile of twelve months of activities was used to accomplish the report. The group was labeled Stamaqui and it counted with 28 components. The activities started in May, 2003. The subjects of the meetings were: health, elderly people’s statute, retirement, among others. Besides the activities taken place there, they also served breakfast, went out for sightseeing and exchanged experiences with participants and professionals. The report aimed at calling managers and health professionals’ attention about getting old as well as the possibility of enlarging concepts and encouraging investments directed to this parcel of the population so that they would maintain a healthy way of living although they have some illness and poor conditions of life.